Promises and pitfalls: the SIEV 221 incident and its aftermath. (2017) - Schloenhardt, Andreas; Johnston, James
On 15 December 2010, 50 asylum seekers drowned when the wooden fishing vessel used to take them from Indonesia to Australia, referred to as SIEV 221 by Australian authorities, crashed against the cliffs of Christmas Island and sank. This incident, which unfolded before the eyes of many locals and was broadcast around the world, shocked the Australian public and led to calls for a radical change of Australia's response to irregular maritime arrivals and migrant smuggling. This research note documents and examines the background and events of the SIEV 221 tragedy and its aftermath, including relevant official reviews, inquests, criminal and civil proceedings. The paper explores the pitfalls that led to this incident and assesses the response to the tragedy against the promises made by the Australian Government at that time.